ANALISIS METODOLOGIS PERAN KAIDAH FIQIH DALAM INTERPRETASI HADIS AHKAM DAN IMPLIKASINYA TERHADAP HUKUM KELUARGA ISLAM - Mohamad Sar'an; Sahril Sidik (USRAH: Jurnal Hukum Keluarga Islam, 2026)
Hadith Ahkam (legal hadiths) are the second primary source in Islamic law, particularly in the field of Family Law (Ahwal Syakhsiyyah). However, understanding Hadith Ahkam cannot always be done literally, given the diversity of wording, context (asbab al-wurud), and potential ta'arudh (contradictions) between arguments. Fiqh principles (Al-Qawa'id al-Fiqhiyyah), as general principles derived from the Qur'an and Sunnah, serve as a crucial methodological tool (manhaj) in the process of istinbath (derivation) and interpretation of law. This study aims to analyse the function and role of Fiqh Principles in understanding Hadith Ahkam and their implications for the establishment of contemporary Islamic Family Law. Using qualitative research methods through library research and the usul fiqh approach, this study found that Fiqh Rules such as Al-Masyaqqah Tajlib at-Taysir (Difficulty brings ease), Ad -Dhararu Yuzal (harm must be eliminated), and Al-'Adah Muhakkamah (customs can become law) function as instruments of tarjih (strengthening one argument over another), takhsis (specifying a general argument), and contextualisation. Its implementation in family law is evident in issues such as marriage guardianship (wali 'adhal), divorce rights, alimony, and child custody (hadhanah), where the application of these principles allows Islamic law to remain relevant, adaptive, and oriented towards public interest (maqasid al-syari'ah